ISD1, an Insertion Element from the Sulfate-Reducing Bacterium Desulfovibrio vulgaris Hildenborough: Structure, Transposition, and Distribution - Fu, Rongdian (American Society for Microbiology, 1998)
Insertion element ISD1, discovered when its transposition caused the insertional inactivation of an introduced sacB gene, is present in two copies in the genome of Desulfovibrio vulgaris Hildenborough. Southern blot analysis indicated at least two insertion sites in the sacB gene. Cloning and sequencing of a transposed copy of ISD1 indicated a length of 1,200 bp with a pair of 44-bp imperfect inverted repeats at the ends, flanked by a direct repeat of the 4-bp target sequence. AAGG and AATT were found to function as target sequences. ISD1 encodes a transposase from two overlapping open reading frames by programmed translational frameshifting at an A(6)G shifty codon motif. Sequence comparison showed that ISD1 belongs to the IS3 family. Isolation and analysis of the chromosomal copies, ISD1-A and ISD1-B, by PCR and sequencing indicated that these are not flanked by direct repeats. ISD1-A is inserted in a region of the chromosome containing the gapdh-pgk genes (encoding glyceraldehyde-3-phosphate dehydrogenase and phosphoglycerate kinase). Active transposition to other loci in the genome was demonstrated, offering the potential of a new tool for gene cloning and mutagenesis. ISD1 is the first transposable element described for the sulfate reducers, a large and environmentally important group of bacteria. The distribution of ISD1 in genomes of sulfate-reducing bacteria is limited. A single copy is present in the genome of D. desulfuricans Norway.